UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN PEGAGAN (Centella asiatica (L.) Urb.) TERHADAP BAKTERI Methicillin Resistant Staphylococcus aureus - Muhammad Dani Riano; Annora Rizky Amalia; Yunita Dian Permata Sari (Program Studi D3 Farmasi Politeknik Indonusa Surakarta, 2023)
MRSA (Methicillin-Resistant Staphylococcus aureus) is one of the gram-positive bacteria that can cause pneumonia. The pegagan plant (Centella asiatica (L.) Urb.) is currently being planted by many people. pegagan leaves have antibacterial activity against bacteria such as Staphylococcus aureus, Staphylococcus mutans, and Escherichia coli. The purpose of this study is to determine whether there is antibacterial activity in pegagan leaves against methicillin-resistant Staphylococcus aureus bacteria. The extraction of pegagan leaf simplisia was carried out by the maceration method. The extract was made with 3 concentrations: 20% b/v, 40% b/v, and 80% b/v. The research method of antibacterial activity testing was carried out by disk diffusion. In this study, the positive control was vancomycin. As for the negative control, a 10% DMSO solution was used. In this study, it was found that the results of pegagan leaf extract had an average inhibition of 20% concentration of 8.75 mm or resistant, 40% concentration of 10.58 mm or resistant, 60% concentration of 11.5 mm or resistant, and a positive control of 18.91 mm or intermediate against MRSA (Methicillin Resistant Staphylococcus aureus) bacteria.